PENGARUH IKLIM KOMUNIKASI ORGANISASI DAN GAYA KOMUNIKASI PIMPINAN TERHADAP KINERJA PEGAWAI PTS DI RIAU - Hendra Hidayat; Lisa Anggraini; M Ridha; Sami’an Sami’an; Aminah Swarnawati (Jurnal Pustaka Komunikasi, 2022)
This study aims to analyze the influence of organizational communication climate and also the influence of leadership communication style on employee performance in one of the Riau Private Universities. The research method used in this study is descriptive analysis to provide an overview of respondents and quantitative analysis using multiple linear regression analysis models. The theory used is Organizational Communication Theory and organizational climate theory. The results of this study found that the communication climate in one of Riau's private universities is positive. Likewise, the leadership's communication style which is based on equality (The Equilitarian Style), makes the performance of employees have high trust between employees and leaders. Decisions are made based on mutual agreement, honesty, listening to each other both up and down, and mutual attention for high performance. The influence of a leadership style based on equality (The Equilitarian Style), also makes the organizational climate more responsive, responsible, and integrated and consistent accountability